An encounter with the enigma some philosophical reflections on Hosiah Chipanga’s music - Rwafa, Urther (Taylor & Francis (Routledge), 2016)
Hosiah Chipanga is dubbed one of the most controversial musicians to have emerged in post-independent Zimbabwe. His music strongly condemns acts of corruption, avariciousness, bribery, nepotism and political power struggles that threaten to tear apart the moral fibre of the Zimbabwean society. Through the songs “Gushungo”, “Dafi” and “Vatsigiri vangu”, Chipanga attempts to salvage truth and sanity out of the “debris” of moral laxity that makes some Zimbabweans fail to go beyond their own limitations. This epistemic search for the “truth” makes Chipanga’s music generate new levels of social, economic and political consciousness at a time when all hope on redeeming Zimbabwe from possible self-destruction seemed to have been lost. Through what one can call “painful political truth” and “liberation theology”, Chipanga calls forth for Zimbabweans to reflect upon their lives and desist from the habit of “blame shifting” by confronting the problems that afflict them.